Implementasi Algoritma Apriori terhadap Kombinasi Pola Penjualan Kuliner Sidamanik Square - Fachrul Rodzy; Ihda Innar Ridho (LPPM STIKOM Tunas Bangsa, 2021)
Data mining is an artificial intelligence that is used to process a lot of data. In data mining, there is one algorithm, namely the Apriori algorithm, which is the most famous algorithm for finding high frequency patterns. For this reason, this algorithm can combine items or items sold at Sidamanik Square Culinary Tour. The resulting apriori algorithm will be implemented and tested with the Tanagra application. This research was conducted to obtain a combination pattern of purchases at Sidamanik Square which is useful for sellers to find out patterns that affect sales and merchandise inventory, namely Penyet Chicken + Rice and Bakso Bakar, namely 60% and Chicken Satay and Bakso Bakar, namely 55.56%.